Answer:
k = 6 or k = -6
Explanation:
The standard form of the quadratic equation is
....[1]
The roots of this equation can be determined using the quadratic formula:
When
there is one real root
When
there are two real roots
When
there are two imaginary roots
First let's convert the equation
into its standard form by multiplying both sides by x
We get
[2]
By comparing this standardized form to the general standard form we can see that the coefficient of x², namely a is 1, the coefficient of x, namely b is k and c is 9
So we have
a = 1
b = k
c= 9
Since we are given that there is only one root and therefore b²-4ac = 0 lets plug in these values of a, b and c
We get k² - 4·1·9 = 0
==> k² - 36 = 0
==> k² = 36
==> k = ±√36
===> k = ±6
So the two possible values of k are k = 6 and k = -6
So the equations become
x² + 6x + 9 = 0 whose roots are x = -3 and x = -3
and
x² -6x + 9 = 0 whose roots are x = 3, x = 3
In both cases the roots are the same
Hope that helps